AN ASSESSMENT OF EASE OF ADMINISTRATION PRINCIPLES IN ARTICLE 22 INCOME TAX POLICY ON GOLD BULLION IN BULLION BUSINESS ACTIVITIES - Dessy Amelia Herianti; Maria R.U.D. Tambunan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the design of Article 22 Income Tax policy on gold bullion transactions within bullion business activities as regulated under Minister of Finance Regulations Number 51 and 52 of 2025, with a particular focus on its alignment with the principle of ease of administration. This study employs a qualitative approach using a literature review of academic studies, regulatory documents, and previous research findings. The analysis focuses on the policy design rather than its empirical implementation. The findings indicate that the revised withholding mechanism, particularly the designation of bullion financial service institutions as withholding agents, improves the structure of tax collection and reduces overlapping obligations. Based on the principle of ease of administration, the policy demonstrates improvements in four key dimensions, namely certainty, efficiency, convenience, and simplicity. The policy enhances clarity in regulatory provisions, reduces administrative and compliance burdens, aligns tax collection with transaction timing, and simplifies the overall structure of taxation on gold bullion transactions. The study recommends further refinement of regulatory design to accommodate potential developments in bullion business activities, particularly in relation to more diverse transaction patterns. Further empirical research is needed to assess the broader implications of the policy.